An Analysis of Code Mixing in Lazuardy Printing TikTok Account - Ince Dian Aprilyani Azir (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The goal of this research was to determine the types of code-mixing employed in Lazuardy's Tiktok account, as well as the variables that influence code mixing. This research was a descriptive qualitative analysis that aimed to characterize the many types of code-mixing and the elements that influence them. The information was gathered through English and Indonesian code mixing texts on Lazuardy's Tiktok account @lazuardy.printing, as well as an interview with the CEO of PT Lazuardy Global Service, in order to identify the reasons and categorize the different forms of code mixing. As a result of the study, the researcher discovered a total of 139 Indonesian English code mixing in Lazuardy's Tiktok, with 84 data representing 60% of word insertions, 41 data representing 30% of phrase insertions, 11 data representing 8% of hybrid insertions, and 3 data representing 2% of clause insertions. According to the report, code mixing is utilized for two reasons. The first reason is that the younger generation is classified as the segmented market of the company. Another goal is to present Lazuardy's products, which will be largely written in English.